A Review of Desmopressin Use in Bleeding Disorders: An Unsung Hero? - Benjamin Reardon; Leonardo Pasalic; Emmanuel J. Favaloro (Biomolecules, 2025)
As a synthetic analogue of vasopressin, desmopressin or DDAVP has well established hemostatic properties. We present a review of DDAVP and summarize the clinical and laboratory evidence for its use in hemophilia A, von Willebrand disease (VWD), platelet function disorders, uremia, liver cirrhosis, and pregnancy, followed by illustrative examples of its broad efficacy from our local practice. In brief, DDAVP acts to release von Willebrand factor (VWF) and factor VIII from endogenously stored reserves, thereby correcting plasma deficiencies present in mild to moderately affected patients with hemophilia A and VWD. Thus, DDAVP represents a non-transfusional therapy for these disorders. Typically, a trial of DDAVP is arranged to assess individual responsiveness before employing DDAVP clinically, since there is individual variation in responsiveness. Thereafter, DDAVP can be utilized in responsive patients for clinical use and provides a factor replacement sparing strategy in these patients for some clinical situations. Nevertheless, DDAVP is best applied as a factor replacement sparing strategy, especially for minor procedures or short-term use.